2020
DOI: 10.1002/mawe.201900105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Al‐Ni powder addition on dissimilar friction stir welding between AA7075‐T6 and 304 L

Abstract: Friction stir welding between AA7075‐T6 aluminum alloy and 304 L stainless steel sheet metal was performed with the addition of Al−Ni powder between the joining interfaces to increase the joining performance. The welding tool was rotated at 200 min−1 to 800 min−1 with the constant traverse speed of 25 mm/min. The resulting joint interfaces were analyzed using a field emission‐scanning electron microscope and energy‐dispersive x‐ray spectroscopy analysis. The tensile strength was greater for the Al−Ni powder ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…They also found that tool offset is critical to the success of joints, in agreement with Jabraeili et al [50]. Muhamad et al [52] investigated the effect of the addition of Al-Ni powder on the performance of Al 7075-T6/AISI 304L FSWed butt joints. They found that the Al-Ni powder addition increased the tensile strength due to the increased contact at the interface during lower tool rotational speeds.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…They also found that tool offset is critical to the success of joints, in agreement with Jabraeili et al [50]. Muhamad et al [52] investigated the effect of the addition of Al-Ni powder on the performance of Al 7075-T6/AISI 304L FSWed butt joints. They found that the Al-Ni powder addition increased the tensile strength due to the increased contact at the interface during lower tool rotational speeds.…”
Section: Introductionsupporting
confidence: 64%
“…The surface appearance of the welded joints became smoother as the rotational speed of the tool was raised from 300 to 500 RPM, and then the weld failed at a rotation speed of 600 RPM. It is well documented that rotational speed and traverse speed have a direct effect on the thermal history of the FSWed joints [52]. This is attributed to an increase in heat input due to the tool rotation speed increase.…”
Section: Surface Appearance and Macrostructurementioning
confidence: 99%
See 1 more Smart Citation
“…This method is successfully used in many industries, including aviation, automotive, shipbuilding, spacecraft or railways [2,3]. FSW treatment has great potential for joining similar materials such as aluminum [4,5], copper [6], steel [7] and dissimilar materials such as aluminum and steel [8,9], aluminium and copper [10,11] or aluminium and titanium [12]. In the literature, it can be fi nd also tests of welding of dissimilar alloys with diff erent thicknesses [13].…”
Section: Introductionmentioning
confidence: 99%
“…In latest years, different researchers focused their studies on the production of reinforced aluminium dissimilar alloys. Muhamad et al [13] produced dissimilar AA7075-AISI304 FSW-joints investigating the effect of the addition of a different amount of Al-Ni powder into the joint-line. The authors detected a metallurgical reaction as an effect of the reinforcing addition, thus promoting an increase of the tensile properties of the joint; however, they found that the selection of specific process parameters, in this case low rotational speed, is fundamental to obtain the desired increase in the static mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%